Cover Image - Qingshuang Zhang; Hongwei Yang; Tsegay Teame; Chao Ran; Yalin Yang; Yuanyuan Yao; Qianwen Ding; Shubin Liu; Shengkang Li; Zhen Zhang; Zhigang Zhou (Reviews in Aquaculture, 2024)
The cover image is based on the Review Article Immune disorders induced by improper use of dietary immunostimulants in aquatic animals: Research progress and prospective solutions by targeting gut microbiota by Qingshuang Zhang and Hongwei Yang et al., https://doi.org/10.1111/raq.12852 . [Correction added on 27 March 2024, after first online publication: Cover image has been changed] image